Global legal skills as a universal language of lawyers - Creciun, Natalia (CEP USM, 2024)
The profession of the lawyer seems to be national limited, due to the fact that future lawyers are trained through acquisition of knowledge on national legislation understanding and interpretation. However, empirical findings prove that lawyers need to be internationally adapted, legal concepts and standards, and value constants being the foundations of solid legal training. Thus, the purpose of the paper is to shape pillars and directions for reviewing current methodologies of teaching-learning-evaluating process in law schools, so as to enhance global legal skills, as a universal language for today’s lawyers. Globally adapted and resilient lawyers are able to contribute, both professionally and empathetically, to ensuring well-being and security of individuals

Profesia de jurist pare să fie limitată la nivel național, datorită faptului că viitorii juriști sunt pregătiți prin dobândirea de cunoștințe despre înțelegerea și interpretarea legislației naționale. Cu toate acestea, constatările empirice demonstrează că juriștii trebuie să fie adaptați la nivel internațional, conceptele, standardele juridice și constantele valorice fiind bazele unei pregătiri juridice solide. Astfel, scopul lucrării este de a modela piloni și direcții de revizuire a metodologiilor actuale de predare-învățare-evaluare la facultățile de drept, astfel încât să consolideze competențele juridice globale, ca limbaj universal pentru juriștii de astăzi. Juriștii rezilienți, adaptați la nivel global sunt capabili să contribuie, atât profesional, cât și empatic, la asigurarea bunăstării și securității persoanelor.
COMPETENȚELE JURIDICE GLOBALE CA LIMBAJ UNIVERSAL AL JURIȘTILOR
Keywords: adaptability; global legal skills; professional well-being; resilient lawyers; social well-being; adaptabilitate; competențe juridice globale; bunăstare profesională; juriști rezilienși; bunăsstare socială